2006
DOI: 10.1113/jphysiol.2006.118703
|View full text |Cite
|
Sign up to set email alerts
|

Modelling spinal circuitry involved in locomotor pattern generation: insights from deletions during fictive locomotion

Abstract: The mammalian spinal cord contains a locomotor central pattern generator (CPG) that can produce alternating rhythmic activity of flexor and extensor motoneurones in the absence of rhythmic input and proprioceptive feedback. During such fictive locomotor activity in decerebrate cats, spontaneous omissions of activity occur simultaneously in multiple agonist motoneurone pools for a number of cycles. During these 'deletions', antagonist motoneurone pools usually become tonically active but may also continue to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
372
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 350 publications
(394 citation statements)
references
References 71 publications
17
372
1
4
Order By: Relevance
“…A similar conclusion about separation of rhythm and motoneuron activation duties arose from intracellular studies of deletions of scratch reflex activity in the turtle (Robertson and Stein, 1988). Our observations on deletions and on the ability of sensory stimulation to alter phase switching within the ongoing step cycle without changing the phase of the post stimulation rhythm (e.g., Guertin et al, 1995;Perreault et al, 1995;Stecina et al, 2005) led to the proposal for a two-level CPG (Lafreniere-Roula and McCrea, 2005;Rybak et al, 2006a). It was recently suggested that a single-level CPG could produce non-resetting deletions if there were a powerful control mechanism that could regulate synaptic transmission between excitatory CPG interneurons and motoneurons (Kiehn, 2006).…”
supporting
confidence: 57%
See 3 more Smart Citations
“…A similar conclusion about separation of rhythm and motoneuron activation duties arose from intracellular studies of deletions of scratch reflex activity in the turtle (Robertson and Stein, 1988). Our observations on deletions and on the ability of sensory stimulation to alter phase switching within the ongoing step cycle without changing the phase of the post stimulation rhythm (e.g., Guertin et al, 1995;Perreault et al, 1995;Stecina et al, 2005) led to the proposal for a two-level CPG (Lafreniere-Roula and McCrea, 2005;Rybak et al, 2006a). It was recently suggested that a single-level CPG could produce non-resetting deletions if there were a powerful control mechanism that could regulate synaptic transmission between excitatory CPG interneurons and motoneurons (Kiehn, 2006).…”
supporting
confidence: 57%
“…when inhibition is blocked. We suggest that the flexor-extensor synchrony that follows the suppression of inhibition results from excitatory interconnections between the half-centers (Rybak et al, 2006a). Such connections might be analogous to those between excitatory CPG neurons in the lamprey (see Cangiano and Grillner, 2005).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…While McCrea and colleagues present some compelling evidence in support of a two-layer model, their evidence that the rhythm-generating layer is organised as half-centres is much less convincing. These investigators rely on spontaneous (Lafreniere-Roula and McCrea, 2005;Rybak et al, 2006a) or evoked (Rybak et al, 2006b) "deletions" of activity in single motor nerves that either are ("resetting" deletions) or are not ("non-resetting" deletions) associated with disruptions of rhythm. They reason that since these non-resetting deletions can be seen in either flexor or extensor muscle nerves, the rhythm-generating layer must excite both the flexor and extensor pattern formation half-centres.…”
Section: Pattern Formation and Rhythm-generating Modulesmentioning
confidence: 99%